LOCAL WISDOM OF BANJAR PEOPLE IN CARRYING OUT SALE AND PURCHASE CONTRACTS ACCORDING TO ISLAMIC ECONOMIC LAW - Muhammad Syarif Hidayatullah; Rahmat Fadillah; Rusdiyah (El-Iqthisadi, 2025)
Abstract This paper aims to describe the local wisdom of the sale and purchase contract of the Banjar people according to sharia economic law based on Shafi’iyah fiqh’s perspective, which interacts with customs in the local wisdom. The research method was normative legal research with a conceptual approach. The local wisdom of the sale and purchase contract of the Banjar people, which was deeply rooted in society, was the words tukar-jual and barelaan. The words tukar-jual, according to sharia economic law, were categorized as shighat (ijab and qabul) in the contract, and the expression barelaan was an expression of asking for willingness, which represented one of the principles of sharia contract law that must be implemented, namely the principle of ‘an taradhin (mutual consent). These words of tukar-jual and barelaan showed the interaction between custom and Shafi’i jurisprudence because, in the Shafi’i school of thought, a strong opinion stated that sales and purchases were considered valid when committing through verbal ijab and qabul; under circumstances when valid sales and purchase could be applied with mutual consent. Furthermore, consent is something that cannot be seen physically. In the Shafi’i school of thought, consent is defined through verbal statements, indicating pleasure’s fulfillment from both parties. The expression of barelaan in Banjar people, apart from entering into a contract through tukar-jual, is also a way to express approval.  Keywords: Contract; Banjar People; Local Wisdom; Sale and Purchase